2013
DOI: 10.1021/es302959h
|View full text |Cite
|
Sign up to set email alerts
|

Spatially-Explicit Life Cycle Assessment of Sun-to-Wheels Transportation Pathways in the U.S.

Abstract: Growth in biofuel production, which is meant to reduce greenhouse gas (GHG) emissions and fossil energy demand, is increasingly seen as a threat to food supply and natural habitats. Using photovoltaics (PV) to directly convert solar radiation into electricity for battery electric vehicles (BEVs) is an alternative to photosynthesis, which suffers from a very low energy conversion efficiency. Assessments need to be spatially explicit, since solar insolation and crop yields vary widely between locations. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Such geographical and regional variances are difficult to capture using average or national values. Therefore, with regional and spatially representative life cycle assessments of bioenergy systems still evolving [10,[15][16][17][18], the use of three regional contexts were proposed in order to support more regional and spatial life cycle thinking 2 for assessing regional bioenergy production systems [19].…”
Section: Assessments Of Bioenergy Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such geographical and regional variances are difficult to capture using average or national values. Therefore, with regional and spatially representative life cycle assessments of bioenergy systems still evolving [10,[15][16][17][18], the use of three regional contexts were proposed in order to support more regional and spatial life cycle thinking 2 for assessing regional bioenergy production systems [19].…”
Section: Assessments Of Bioenergy Systemsmentioning
confidence: 99%
“…To simplify such complexity, for life cycle assessment, all environmental burdens are aggregated across the full life cycle of a product (i.e., from the thousands of global sites with associated production activities), removing the regional or spatial patterns relating to the production and distribution of such environmental burdens [22]. However, with many environmental burdens associated with bioenergy production occurring at the regional level [13,23,24], there is a need to produce more regional and spatially representative life cycle assessments of bioenergy systems [10,15,16,18,25]. Therefore, the challenge is to find a balance between the increased focus on regional activities and direct environmental burdens associated with bioenergy production (e.g., emissions produced within the regional foreground) and the requirement to account for the nonregional environmental burdens also associated with such regional bioenergy production (i.e., emissions produced upstream, not within the regional foreground, but elsewhere outside the region).…”
Section: Regionally Contextualised Life Cycle Thinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Geyer et al (2010) proposed coupling GIS and LCA for biodiversity assessment of land use and biofuels in the U.S. In their 2013 study of biofuels, they identified a wide variance in direct land use impacts for biomass-based pathways ranging from 5m 2 /100 km to 100m 2 /100 km (i.e., direct land use impacts expressed in m 2 /100 km driven) (Geyer et al 2013).…”
Section: Spatial Lcasmentioning
confidence: 99%
“…Energy Independence and Security Act (EISA) requires finding economically viable, socially acceptable, and environmentally sustainable production strategies to grow bioenergy crops. Today, the major commercial feedstock for the U.S. ethanol industry is corn grain, with over 40% of the crop used for ethanol production [1,2]. To minimize food, feed and energy competition, EISA mandates that a large percentage of fuel originate from lignocellulosic feedstock by 2022.…”
Section: Introductionmentioning
confidence: 99%